P11.30.A Stereotactic Radiosurgery (SRS) for brain metastases in breast cancer: An evaluation of outcomes at a UK tertiary centre. (5th September 2022) - Abdul Haris, P; Brazil, L; Blythe, K; Chia, K; Hassan, S; Loganathan, T; Smith, D; Swampillai, A; Al-Salihi, O
Abstract: Background: Brain metastases (BM) occur in approximately 10-30% of patients with breast cancer (BC). Patients with advanced breast cancer are living longer, and the incidence of BM are increasing. Stereotactic Radiosurgery (SRS) has emerged as a strategy to treat BM. We evaluated the outcomes and potential prognostic factors of patients with BM treated with SRS. Material and Methods: Retrospective review of patients treated with linac-based SRS for BM from BC in a single tertiary centre between August 2017-September 2021. Overall survival (OS), intracranial progression-free survival (IPFS), and prognostic factors were evaluated using Kaplan-Meier analysis, log-rank test, and Cox proportional-hazards model. Results: 76 patients were included in the analysis. Out of these, 56 had first-line local treatment with SRS, either as primary (n=34) or adjuvant to surgery (n=22). Median age was 58 years old (range 37-86), and 88% had PS 0/1. One-year survival rate was 56%. Median OS and IPFS from SRS was 16 months (95% CI 8-24) and 7 months (95% CI 2-12), respectively. However, there were significant differences in OS (p<0.001) and IPFS (p=0.001) based on molecular subtypes. Patients with triple-negative breast cancer (TNBC) (n=14) had median OS of 7 months (95% CI 2-12), ER+/HER2- (n=22) median OS of 22 months, ER-/HER2+ (n=8) median OS of 4 months (95% CI 0-9), and ER+/HER2+ (n=11) median OS of 36 months. Similar trend was seen with IPFS. Patients with progressive extracranial disease compared to stable disease had shorter median OS (4 months vs 23 months, HR 2.4, p=0.01) and median IPFS (4 months vs 13 months, HR 2, p=0.03). Age ≥65 years was associated with shorter median OS (4 vs 23 months, HR 2.3, p=0.02). Patients with ≥4 brain metastases had shorter IPFS (4 months vs 11 months, HR 2.4, p=0.012), but no significant difference in OS. Volume of metastases did not affect outcome in this series. 30% of patients progressed intracranially after first-line SRS. 94 % had out-of-field recurrences, and 6% in-field recurrences. 59% had further SRS, 12 % WBRT, 6% surgery, and 23% had no further local treatment. 26 patients had second-line local treatment with SRS after first-line SRS (n=9), WBRT (n=9), or surgery +/- WBRT (n=8). There were no significant differences in outcome based on the modality of first-line local treatment. Conclusion: SRS is an effective treatment for BM from BC. There were significant differences in survival based on age, molecular subtypes, and extracranial disease status.